FAKTOR-FAKTOR YANG MENGHAMBAT MASYARAKAT UNTUK BERJALAN KAKI DAERAH PERKOTAAN - NI KOMANG INDRA MAHAYANI; PUTRI AYU DEVY PERMATA SARI (Universitas Mahasaraswati K. Mataram, 2024)
Walking is very important in cities as it helps people to travel from one place to another. Urban areas in Bali are experiencing rapid development as tourism normalises, gradually entering a process of urban renewal. Improving the quality of the pedestrian environment is an important issue. The purpose of this research is to study how a person's physical condition, concepts, and activities affect their physical character and interest in walking. A quantitative method was used using randomly distributed open-ended questionnaires. Pedestrian criteria and facilities will be the source of data categorised in inhibiting pedestrians. A person who wants to walk should have good access and well-maintained facilities so that urban areas can be specialised for pedestrian paths.